Hak dan Kewajiban Kepala Tanah Sῑma dalam Masa Majapahit - Machi Suhadi (Balai Arkeologi Yogyakarta, 1994)
The study of inscriptions related to the rights and obligations in Old Javanese society is only a small part of sociological aspects. There are still many other aspects of sociology still untouched, both from the ancient society of Javanese, Balinese, Sundanese, and another part of Archipelago. The right of sima landlord is stated in the inscription, while the obligations sima landlord is not always stated in the description of the inscription. This makes the study of sima quite difficult because the elements associated with this kind of obligation are often disguised.